A Delphi study assessing the utility of quality improvement tools and resources in Australian primary care. (18th April 2016) - Upham, Susan J; Janamian, Tina; Crossland, Lisa; Jackson, Claire L
Abstract: Objectives: To determine the relevance and utility of online tools and resources to support organisational performance development in primary care and to complement the Primary Care Practice Improvement Tool (PC‐PIT). Design: A purposively recruited Expert Advisory Panel of 12 end users used a modified Delphi technique to evaluate 53 tools and resources identified through a previously conducted systematic review. The panel comprised six practice managers and six general practitioners who had participated in the PC‐PIT pilot study in 2013–2014. Tools and resources were reviewed in three rounds using a standard pre‐tested assessment form. Recommendations, scores and reasons for recommending or rejecting each tool or resource were analysed to determine the final suite of tools and resources. The evaluation was conducted from November 2014 to August 2015. Results: Recommended tools and resources scored highly (mean score, 16/20) in Rounds 1 and 2 of review ( n = 25). These tools and resources were perceived to be easily used, useful to the practice and supportive of the PC‐PIT. Rejected resources scored considerably lower (mean score, 5/20) and were noted to have limitations such as having no value to the practice and poor utility ( n = 6). A final review (Round 3) of 28 resources resulted in a suite of 21 to support the elements of the PC‐PIT. Conclusions: This suite of tools and resources offers one approach to supporting the quality improvement initiatives currently in development in primary care reform.